Bureaucrats and Indigenes: Producing and Bypassing Certificates of Origin in Nigeria - (:unkn) unknown (My University, 2015)
In the last three decades, the politics of indigeneity have led to discrimination against and marginalization of non-indigenes as well as numerous violent conflicts between indigenes and non-indigenes in Nigeria. This discrimination, which is based on a localized place of belonging, has today become bureaucratized: local governments produce ‘certificates of indigene’ to identify the origin of their holders. This article looks at the bureaucratic machinery of issuing certificates of origin in two local governments of Oyo State (in the south-west) and the everyday encounters between users and bureaucrats that cannot be reduced to practices of corruption. It looks at the complicated and ambivalent process of identifying a ‘true indigene’; this process is supposed to strengthen local citizenship but it also contributes to the daily functioning of the state and is largely accepted by the majority as part of the state's ‘insidious gentleness’. The article also seeks to understand why official discrimination against non-indigenes is poorly contested locally by assessing the role of these documents in accessing public employment, university places and basic services, and examining whether areas inhabited by non-indigenes are perceived as being neglected or abandoned by the state. Currently, discrimination policies are implemented unequally and in many instances client–patron relationships help sidestep these policies.
Keywords: African Research